GREEN MACHINING ORIENTED TO DIMINISH DENSITY GRADIENT FOR MINIMIZATION of DISTORTION IN ADVANCED CERAMICS - Bukvic, Gill [UNESP]; de Angelo Sanchez, Luiz Eduardo [UNESP]; Fortulan, Carlos Alberto; Fiocchi, A. A. [UNESP]; Marinescu, Ioan Demitrius (Taylor & Francis Inc, 2012)
After sintering advanced ceramics, there are invariably distortions, caused in large part by the heterogeneous distribution of density gradients along the compacted piece. To correct distortions, machining is generally used to manufacture pieces within dimensional and geometric tolerances. Hence, narrow material removal limit conditions are applied, which minimize the generation of damage. Another alternative is machining the compacted piece before sintering, called the green ceramic stage, which allows machining without damage to mechanical strength. Since the greatest concentration of density gradients is located in the outer-most layers of the compacted piece, this study investigated the removal of different allowance values by means of green machining. The output variables are distortion after sintering, tool wear, cutting force, and the surface roughness of the green ceramics and the sintered ones. The following results have been noted: less distortion is verified in the sintered piece after 1mm allowance removal; and the higher the tool wear the worse the surface roughness of both green and sintered pieces.
Keywords: ceramic; density gradient; distortion; green machining; pressing; sintering